Authenticating discourses of "being oneself" on monetary-motivated livestreams. (June 2022) - Hsiao, Chi-hua
Abstract: On Chinese monetary-motivated live broadcasts, during which streamers present a variety of activities such as musical and artistic skills to solicit financial contributions from online viewers, streamers' personal authenticity is a major factor influencing viewer donations and user engagement. Through an ethnographic approach to collect data from livestream channels at the Taiwan-based livestreaming platform, Lang Live, this article examines the authenticating discourses streamers engage to demonstrate that they are being their true selves rather than performing contrived theatrics in order to attract viewers. Specifically, I explore how authenticating discourses are conducted, co-constructed, and negotiated by considering factors including the platform-specific features, streamers' self-expression, and viewer responses. I propose a specific meaning of personal authenticity emerging from users' dynamic interactions, discuss viewers' reasoning behind it, and explore how these perceptions of personal authenticity are linked to Lang Live's communicative affordances and monetary system.